2018
DOI: 10.3201/eid2412.180879
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Avian Influenza A(H5) and A(H9) Viruses in Live Bird Markets, Bangladesh

Abstract: We conducted a cross-sectional study in live bird markets (LBMs) in Dhaka and Chittagong, Bangladesh, to estimate the prevalence of avian influenza A(H5) and A(H9) viruses in different types of poultry and environmental areas by using Bayesian hierarchical logistic regression models. We detected these viruses in nearly all LBMs. Prevalence of A(H5) virus was higher in waterfowl than in chickens, whereas prevalence of A(H9) virus was higher in chickens than in waterfowl and, among chicken types, in industrial b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
83
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(98 citation statements)
references
References 40 publications
8
83
1
Order By: Relevance
“…Indeed, rest days/nights are an important component of long‐term AIV control but are not sufficient alone to eliminate infection (Kung et al, ). Furthermore, risk factor studies in LBMs have shown that having a greater variety of poultry species, including ducks being sold alongside other species, having poor sanitary conditions, storing poultry in floor pens instead of cages and having ≥1 wholesaler trading in LBMs, all increase the odds of having AIV‐infected poultry and/or having AIV‐contaminated environments (Kim et al, ; Kirunda et al, ; Santhia et al, ; Sayeed et al, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, rest days/nights are an important component of long‐term AIV control but are not sufficient alone to eliminate infection (Kung et al, ). Furthermore, risk factor studies in LBMs have shown that having a greater variety of poultry species, including ducks being sold alongside other species, having poor sanitary conditions, storing poultry in floor pens instead of cages and having ≥1 wholesaler trading in LBMs, all increase the odds of having AIV‐infected poultry and/or having AIV‐contaminated environments (Kim et al, ; Kirunda et al, ; Santhia et al, ; Sayeed et al, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Live Poultry Markets (LPMs) in Asian countries act as centres for virus accumulation, amplification and the spread of various infectious diseases such as avian influenza (Fournié, De Glanville, & Pfeiffer, 2012;Fournié, Guitian, Mangtani, & Ghani, 2011). The survey in LPMs in Bangladesh showed high contamination levels for both influenza A type H5 and H9 viruses (Biswas et al, 2018;Hasan et al, 2016;Kim et al, 2018). It has been shown that avian influenza viruses (AIV) are still circulating among poultry populations and have entered into LPMs through the poultry supply chain.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, the proportion of birds positive for the AIV was estimated in Bangladeshi LBMs, including in CCLBMs which are supplied by our farm study population. The proportion of birds positive for H5 and H9 virus reached 1.3% and 8.3 % in backyard chickens, 7.6% and 3.4% in waterfowl (including ducks and geese), 0.9% and 13.1% in broiler chickens, respectively (Kim et al, 2018). In contrast, H9 prevalence was here estimated to be much lower in farmed poultry, and all sampled birds tested negative for H5.…”
Section: Discussionmentioning
confidence: 62%
“…Investigations of HPAI outbreaks have generated insights in possible risk factors associated with sudden deaths of birds (Biswas et al, 2009b;Loth, Gilbert, Osmani, Kalam, & Xiao, 2010;Osmani et al, 2014), but they don't provide information about the circulation of AIV in farmed poultry populations in endemically infected countries. Furthermore, in such countries, studies aiming to assess the level of viral circulation in poultry are generally conducted in LBMs (ElMasry et al, 2017;Kim et al, 2018;Negovetich et al, 2011;Thuy et al, 2016), and rarely in poultry farms. This can partly be explained by the ease of sampling, as birds raised under different production systems are brought together in a single location.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation